Thermal stability of oxygen vacancy stabilized zirconia (OVSZ) thin films - Raza, Mohsin; Boulet, Pascal; Pierson, Jean-François; Snyders, Rony; Konstantinidis, Stéphanos (Surface & coatings technology, 2021)
Thermal stability of reactive magnetron sputter deposited oxygen vacancy stabilized cubic zirconia (OVSZ) thin films containing 16 and 3 at.% oxygen vacancies is reported. Temperature-resolved grazing incidence X-ray diffraction (TR-GIXRD) measurements (200–900 °C) in air and nitrogen atmosphere were performed. TR-GIXRD data show that the deposited films are stable up to 750 °C irrespective of the annealing atmosphere or the oxygen vacancy concentration. However, above 750 °C a fraction of zirconia transforms from cubic to monoclinic structure. This structural transition is explained by the compressive stresses, generated as a result of discrepancy in film-substrate thermal expansion coefficients. Thermal cycling of the deposited OVSZ thin films is also performed at 700 °C and show that films retain their initial cubic structure. •Thermal stability of oxygen vacancy stabilized zirconia (OVSZ) thin films is reported.•OVSZ thin films are stable up-to 750 °C irrespective of annealing ambient (N2 or air) or oxygen vacancy concentration.•Mono-clinic peak appear above 750 °C as a result of compressive stresses.